Swimming against the Current: Reimagining Jewish Tradition in the Twenty-First Century. Essays in Honor of Chaim Seidler-Feller - Myers, David N; Seidler-Feller, Shaul (Academic Studies Press, 2020)
Frontmatter -- Contents -- Introduction: A Portrait of Chaim Seidler-Feller -- Bibliography of Publications by Chaim Seidler-Feller -- Order as Meaning: Juxtaposition in the Bible -- Behind Every Great Prophet Is a Woman: The Women in Exodus 2 in Talmudic Interpretation -- Study of Torah as a Discourse of Violence: Milḥamtah shel Torah, Variations on a Theme -- Discipleship in Rabbinic Literature -- Secular Legal Paradigms and Talmudic Law: Rav Tsa‘ir on Legal Loopholes -- Buber, Scholem, and the Me’or enayim: Another Perspective on a Great Controversy -- On Not Finishing the Work: A Commentary on Avot 2:16 -- The Faith of Abraham -- The Ascent and Decline of the “Historical Jew” -- Divine Command Theory in Jewish Law and Ethics -- Polio Season: Transformations of Philip Roth’s “Jewish Mother” from Sophie Portnoy to Marcia Steinberg -- Go to School, Work, Marry, Have Children, Be Jewish: Jewish Women and Jewish Men in the United States and Israel -- The Day of Reckoning: Max Radin and the Rule of Law in International War Crimes -- Antisemitism: Reflections and Ruminations -- Sovereignty and Ethics in the Thought of Rabbi Ḥayyim David Halevi -- Rabbi Shlomo Goren on the Maimonidean Law of Siege: An Essay on the Ethics of Jewish Warfare -- Invoking the Indigenous, for and against Israel -- Jewish Folk Art and Ideology: The Śimḥat Torah Flag through the Ages -- Meira Wolkenfeld -- Adam Greenwald -- Mayim Bialik -- Jonathan Jacoby -- Laurie L. Levenson -- Edward Feld -- David Berner -- Saul Andron -- List of Contributors